Case report: CD19-directed CAR-T cell therapy combined with BTK inhibitor and PD-1 antibody against secondary central nervous system lymphoma - Wenqi Zhang; Chen Huang; Chen Huang; Ruixia Liu; Huichao Zhang; Weijing Li; Shaoning Yin; Lianjing Wang; Wei Liu; Lihong Liu; Lihong Liu (Frontiers in Immunology, 2022)
Current therapeutic strategies for central nervous system (CNS) relapse of diffuse large B-cell lymphoma (DLBCL) are extremely limited. Secondary central nervous system lymphoma (SCNSL) also shows a grave prognosis and high mortality. This report describes a young female patient with DLBCL and CNS relapse who received low-dose CD19-directed chimeric antigen receptor T (CAR-T) cell therapy followed with Bruton’s tyrosine kinase inhibitor and programmed cell death protein 1 antibody after several lines of chemotherapy. However, limited reports on CAR-T cell therapy are applied for SCNSL, particularly those in combination with targeted agents. The current treatment combination for this case provides a new regimen for CNS relapse from DLBCL.Clinical Trial RegistrationClinicalTrials.gov number, NCT04666168.